Autonomic Dysfunction in Preeclampsia: A Systematic Review - Yousif, Dalia; Bellos, Ioannis; Penzlin, Ana Isabel; Hijazi, Mido Max; Illigens, Ben Min-Woo; Pinter, Alexandra; Siepmann, Timo (Frontiers in Neurology, 2019)
1. Abstract Background: Preeclampsia (PE) is a major obstetric complication that leads to severe maternal and fetal morbidity. Early detection of preeclampsia can reduce the severity of complications and improve clinical outcomes. It is believed that the autonomic nervous system (ANS) is involved in the pathogenesis of PE. We aimed to review the current literature on the prevalence and nature of ANS dysfunction in women with PE and the possible prognostic value of ANS testing in the early detection of PE. Methods: Literature search was performed using Medline (1966–2018), EMBase (1947 – 2018), Google Scholar (1970–2018), BIOSIS (1926-2018), Web of science (1900-2018); CINAHL (1937- 2018); Cochrane Library (Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials (CENTRAL) and Cochrane Methodology Register (1999–2018) Additionally, the reference lists of articles included were screened. Results: A total of twenty-six studies were included in the present review presenting data of 1854 pregnant women. Among these women, 453 were diagnosed with PE 93.6% (424 /453) of which displayed autonomic dysfunction. ANS function was assessed by cardiovascular reflex tests (n=9), heart rate variability (n=11), cardiac baroreflex gain (n=5), muscle sympathetic nerve activity (n=3) and biomarkers of sympathetic activity (n=4). Overall, 21 studies (80.8%) reported at least one of the following abnormalities in ANS function in women diagnosed with PE compared to healthy pregnant control women: reduced parasympathetic activity (n= 16/21, 76%), increased sympathetic activity (n=12/20, 60%) or reduced baroreflex gain (n=4/5, 80%). Some of these studies indicated that pressor and orthostatic stress test may be useful in early pregnancy to help estimate the risk of developing PE. However, autonomic function tests seem not to be able to differentiate between mild and severe PE. Conclusions: Current evidence suggests that autonomic dysfunction is highly prevalent in preeclamptic women. Among autonomic functions, cardiovascular reflexes appear to be predominantly affected, seen as reduced cardiac parasympathetic activity and elevated cardiac sympathetic activity. The diagnostic value of autonomic testing in the prediction and monitoring of autonomic failure in preeclamptic women remains to be determined.